2019
DOI: 10.1145/3314405
|View full text |Cite
|
Sign up to set email alerts
|

Animo

Abstract: We present Animo, a smartwatch app that enables people to share and view each other's biosignals. We designed and engineered Animo to explore new ground for smartwatch-based biosignals social computing systems: identifying opportunities where these systems can support lightweight and mood-centric interactions. In our work we develop, explore, and evaluate several innovative features designed for dyadic communication of heart rate. We discuss the results of a two-week study (N=34), including new communication p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 58 publications
2
46
0
Order By: Relevance
“…A small body of prior work has explored these expressive biosignals, beginning to show that information about another person's biosignals can help facilitate empathy and social awareness [35,38,51] and, in some contexts, a greater sense of intimacy and connection [40,50]. These results point to potential opportunities for expressive biosignals to support interventions for bridging understanding with others, such in contexts in which feeling empathy or closeness with others is challenging (e.g., with members of socially distant groups, or physically remote others).…”
Section: Fannie Liu Geoff Kaufman and Laura Dabbishmentioning
confidence: 99%
See 4 more Smart Citations
“…A small body of prior work has explored these expressive biosignals, beginning to show that information about another person's biosignals can help facilitate empathy and social awareness [35,38,51] and, in some contexts, a greater sense of intimacy and connection [40,50]. These results point to potential opportunities for expressive biosignals to support interventions for bridging understanding with others, such in contexts in which feeling empathy or closeness with others is challenging (e.g., with members of socially distant groups, or physically remote others).…”
Section: Fannie Liu Geoff Kaufman and Laura Dabbishmentioning
confidence: 99%
“…Prior literature suggests the potential for expressive biosignals to affect empathy for others. In particular, several qualitative studies that deploy expressive biosignal systems (both in the wild and in laboratory settings) have demonstrated that people tend to infer and be more aware of a close contact's emotional state through displays of heart rate and skin conductance [35,38,49,51].…”
Section: Expressive Biosignals and Empathymentioning
confidence: 99%
See 3 more Smart Citations